Democratic and Pseudo-Democratic Leadership Styles as Correlate of Sustainability of Community Development Projects in Southwest, Nigeria - Olanipekun, Olubunmi Adebola; Adedokun , Mary Olufunke (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This study explores the relationship between community leadership styles—specifically, democratic and pseudo-democratic styles—and the sustainability of community projects in Southwest Nigeria. Employing a descriptive research design of the survey type, data were collected through self-structured questionnaires administered to 300 community leaders and 1,459 community members across 60 communities in three states. The instruments utilized were the Democratic and Pseudo-democratic Leadership Styles Questionnaire (DPLSQ) and the Sustainability of Community Development Projects Questionnaire (SCDPQ), each designed to gauge respondents' perceptions and attitudes. Descriptive and inferential statistical analyses, including Pearson’s Product Moment Correlation, were employed to analyze the data. Findings revealed a significant discrepancy between democratic leadership ideals and actual practices, with community leaders often failing to involve members in decision-making processes, mobilization, or seeking their opinions on projects. Similarly, pseudo-democratic leadership, characterized by token consultation while disregarding community input, was prevalent. However, while democratic leadership exhibited a moderately positive relationship with project sustainability, pseudo-democratic leadership showed no significant correlation. It was concluded that democratic leadership enhances sustainability, whereas pseudo-democratic leadership undermines it. Recommendations include fostering genuine community participation in project decision-making processes and advocating for democratic leadership styles to ensure project sustainability. These findings underscore the importance of transparent, inclusive governance practices for successful community development initiatives.